Effect of exogenous testosterone on oxidative status of the testes in adult male rats. (5th November 2012) - Tóthová, L.; Celec, P.; Ostatníková, D.; Okuliarová, M.; Zeman, M.; Hodosy, J.
Summary: The aim of this study was to investigate the testosterone‐induced changes in the oxidative status of testes in adult male rats treated either with testosterone or after blockade of androgen receptors with cyproterone acetate. A total of 40 intact rats were divided into four groups: a control group receiving sterile oil, the testosterone group receiving testosterone isobutyras, the cyproterone group receiving cyproterone acetate and the combination group receiving both testosterone isobutyras and cyproterone acetate. Treatments were carried out for 2 days by intramuscular application. Parameters of oxidative stress and the expression levels of the steroidogenic acute regulatory protein (StAR) gene were measured in testes. Significantly increased TBARS and advanced glycation end products (AGEs) levels were found in the testosterone group when compared to the control group. The °1 ferric‐reducing ability of the tissue and total antioxidative capacity were lower in the testosterone group in comparison with the control group. Gene expression analysis revealed significant downregulation of the StAR gene in the testes of rats in the testosterone and combination groups with respect to control animals. In conclusion, administration of exogenous testosterone influences the lipid peroxidation and carbonyl stress and decreases the antioxidant defence in the testes. These data might have implications for male fertility in humans.